Greatwall-Endos-PP2A/B55[Twins] network regulates translation and stability of maternal transcripts in the Drosophila oocyte-to-embryo transition. - Rangone, H.; Bond, L.; Weil, T.T.; Glover, D.M. (Open biology, 2024)
The transition from oocyte to embryo requires translation of maternally provided transcripts that in Drosophila is activated by Pan Gu kinase to release a rapid succession of 13 mitotic cycles. Mitotic entry is promoted by several protein kinases that include Greatwall/Mastl, whose Endosulfine substrates antagonize Protein Phosphatase 2A (PP2A), facilitating mitotic Cyclin-dependent kinase 1/Cyclin B kinase activity. Here we show that hyperactive greatwall[Scant] can not only be suppressed by mutants in its Endos substrate but also by mutants in Pan Gu kinase subunits. Conversely, mutants in me31B or trailer hitch, which encode a complex that represses hundreds of maternal mRNAs, enhance greatwall[Scant] . Me31B and Trailer Hitch proteins, known substrates of Pan Gu kinase, copurify with Endos. This echoes findings that budding yeast Dhh1, orthologue of Me31B, associates with Igo1/2, orthologues of Endos and substrates of the Rim15, orthologue of Greatwall. endos-derived mutant embryos show reduced Me31B and elevated transcripts for the mitotic activators Cyclin B, Polo and Twine/Cdc25. Together, our findings demonstrate a previously unappreciated conservation of the Greatwall-Endosulfine pathway in regulating translational repressors and its interactions with the Pan Gu kinase pathway to regulate translation and/or stability of maternal mRNAs upon egg activation.